Preparation method of nitrogen-doped quantum dots and oil reservoir application of nitrogen-doped quantum dots
By preparing nitrogen-doped quantum dots, the problems of poor dispersion stability and insufficient ability to reduce interfacial tension in ultra-low permeability reservoirs are solved, efficient dispersion and improved wettability in high-temperature and high-salt environments are achieved, and crude oil recovery is improved.
Patent Information
- Application Number
- CN202411760878.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
Existing quantum dots have poor dispersion stability in ultra-low permeability reservoirs, insufficient ability to reduce interfacial tension, and poor effect in improving wetting properties.
A new preparation method of nitrogen-doped quantum dots is adopted. By mixing the carbon source and the nitrogen source, adding alkylamine polyoxyethylene ether, and performing solid phase pyrolysis reaction, a black solid product is obtained, and nitrogen-doped quantum dots are obtained through multiple filtration and dialysis.
In high temperature and high salt environments, nitrogen-doped quantum dots have good dispersion stability, which can effectively reduce oil-water interface tension, improve rock wettability, and improve crude oil recovery, overcoming the shortcomings of existing quantum dots.
Smart Images

Figure CN119551661A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, in particular to a method for preparing nitrogen-doped quantum dots and oil reservoir application thereof. Background Art
[0002] At present, many oil fields have entered the middle and late stages of development. The water content of oil reservoirs is increasing, and the heterogeneity of reservoirs is increasing. The extraction efficiency of traditional oil recovery technology can no longer meet the increasing demand for oil. Therefore, it is urgent to develop a low-cost, high-efficiency new oil recovery technology to solve this problem. Surfactants have the ability to reduce the oil / water interfacial tension, strip crude oil from the rock surface, and drive the remaining oil to flow. However, in low-permeability reservoirs, the emulsion formed by surfactants makes it easy to block the formation. Therefore, more and more nanomaterials are used to improve the recovery rate of low-permeability reservoirs. Nanomaterial oil recovery has been applied to the field of improving crude oil recovery as a new oil recovery technology. Compared with traditional surfactants and polymer materials, nanomaterials have the advantages of small size and easy modification. At the same time, they have the ability to reduce the oil-water interfacial tension and change the wettability of rocks. Among them, quantum dots not only have strong interfacial activity, but also have a size structure below 10nm. They have the ability to enter the tiny pores of dense and low-permeability reservoirs to drive out crude oil, so they have broad application prospects.
[0003] For example, Zhou et al. developed a new type of nanofluid using ultra-small silicon quantum dots (SiQDs) coated with zwitterionic surfactants. The nanofluid has excellent stability and temperature resistance in high-mineralization water, and has excellent performance in reducing interfacial tension and changing rock wettability. Experimental results show that the final recovery of the new nanofluid is 11.7% higher than that of the simple surfactant. Zhao et al. synthesized an active sulfonated silicon quantum dot nanofluid composed of S-SiQDs nanoparticles and dodecyl sulfobetaine (BS) by hydrothermal method. The material has an average particle size of 5.4nm and has excellent temperature and salt resistance. Compared with a single surfactant and a single S-SiQDs nanoparticle, the material has better ability to reduce oil / water interfacial tension, improve wettability and deoiling. Experimental data show that the active S-SiQDs nanofluid can significantly improve the swelling recovery rate to 29.9%.
[0004] Although quantum dots have the characteristics of small size and structure, excellent chemical properties, etc., they have poor stability in high temperature and high salt environments and are prone to agglomeration. They also have shortcomings such as poor dispersion stability in low permeability and ultra-low permeability reservoirs, insufficient ability to reduce interfacial tension, low interfacial film strength, and poor effect in improving wettability. Summary of the invention
[0005] In view of the problems existing in the existing quantum dots, such as poor dispersion stability in ultra-low permeability reservoirs, insufficient ability to reduce interfacial tension, and poor effect of improving wettability, the present invention provides a novel nitrogen-doped quantum dot.
[0006] The novel nitrogen-doped quantum dots provided by the present invention have the following steps for preparing the same:
[0007] S1. Mix the carbon source and the nitrogen source, and seal and stir in a water bath at 45°C for several minutes to mix the materials evenly to obtain a mixture.
[0008] S2. Add alkylamine polyoxyethylene ether to the mixture in a water bath at 55-65°C, seal and stir for 10-20 minutes to form a light yellow block, then transfer to a high-temperature and high-pressure reactor, heat to 150-220°C and maintain the temperature for 45-120 minutes to carry out solid-phase pyrolysis reaction to obtain a black solid product.
[0009] S3. Grind the black solid product into powdery particles and disperse them in n-hexane, wash them, and preliminarily remove the unreacted substances; then add anhydrous ethanol and further wash them in combination with ultrasonic waves to obtain a black powdery product.
[0010] S4. Dissolve the black powder product in deionized water, filter and purify it multiple times using a 0.22-micron filter membrane, transfer the obtained black liquid to a 100KD ultrafiltration tube, and centrifuge to remove large particles; add the clear liquid from the ultrafiltration outer tube to a dialysis bag with a molecular weight cutoff of 1000Da, seal it and dialyze it in deionized water to completely remove unreacted raw material small molecules, and finally dry the solution in the dialysis bag to obtain a black powder solid, which is the nitrogen-doped quantum dots.
[0011] Preferably, the carbon source is citric acid and the nitrogen source is urea.
[0012] Preferably, the alkylamine polyoxyethylene ether is selected from one or more combinations of ethylamine polyoxyethylene ether, dodecylamine polyoxyethylene ether, hexadecylamine polyoxyethylene ether, and octadecylamine polyoxyethylene ether. The mass ratio of the alkylamine polyoxyethylene ether to the nitrogen source is 1:1.
[0013] Preferably, in step S4, the centrifugal separation is performed at a speed of 4000 r / min and for 20 min.
[0014] The present invention also provides an application method of the nitrogen-doped quantum dots, wherein a nitrogen-doped quantum dot dispersion having a mass percentage concentration of 0.05-0.1% is prepared with an on-site injection fluid; the nitrogen-doped quantum dot dispersion is injected into a target reservoir, the well is kept cold for 1-2 days, and then the well is opened for production. The on-site injection fluid is supercritical CO2 or formation water.
[0015] The nitrogen-doped quantum dot dispersion prepared by the on-site injection fluid is used as a quantum dot oil displacement agent and is suitable for various oil reservoirs such as low permeability (ultra-low permeability), tight oil reservoirs, and shale oil reservoirs. It has good dispersion stability in high temperature and high salt environments. After entering the reservoir pores, the nitrogen-doped quantum dots are enriched at the oil-water interface. The hydrophilic groups exist in the water phase, and the hydrophobic groups exist in the oil phase, replacing the original oil-water interface, reducing the friction between the oil and water phases, and thus reducing the oil-water interfacial tension to 10 -1 mN / m, and the nitrogen-doped quantum dots can form a colloidal layer with increased local viscosity at the oil / water interface, enhance the ability of the oil / water interface film to recover and block deformation, and achieve efficient fluidity control. In addition, the nitrogen-doped quantum dots can improve the wettability of rocks, make the rock surface highly water-wet, peel off the oil droplets adsorbed on the rock surface, increase capillary force, and improve the efficiency of crude oil displacement, thereby improving the crude oil recovery rate.
[0016] Compared with the prior art, the present invention is beneficial in that:
[0017] (1) The novel nitrogen-doped quantum dots prepared in the present invention can spontaneously accumulate at the oil / water interface to form a colloidal layer with locally increased viscosity, which is beneficial to fluidity control, prevents the occurrence of viscous fingering, and achieves efficient fluidity control.
[0018] (2) The nitrogen-doped quantum dots can enhance the ability of the oil / water interface film to recover and block deformation based on their own elastic properties, thereby improving the strength of the oil / water interface film and improving the microscopic oil displacement efficiency.
[0019] (3) Nitrogen-doped quantum dots have good water solubility, stability and dispersibility, and the quantum dot solution can be directly prepared with the on-site injection fluid, and the on-site injection water can be supercritical CO2 or formation water.
[0020] (4) Nitrogen-doped quantum dots have both hydrophilic and hydrophobic groups, which can be enriched at the oil-water interface. The hydrophilic groups exist in the water phase, and the hydrophobic groups exist in the oil phase, which effectively reduces the friction between the oil and water phases, thereby reducing the oil-water interfacial tension.
[0021] (5) Nitrogen-doped quantum dots can also change the wettability of rocks (the rock surface is strongly water-wet), improve capillary drainage, and thus increase crude oil drainage efficiency.
[0022] (6) The tiny size of nitrogen-doped quantum dots can enter low-permeability (ultra-low-permeability) reservoirs, tight reservoirs, and shale reservoirs, and can enter tiny pores less than 10 nm. The synergistic effect formed by surfactant grafting modification on the basis of quantum dots has excellent stability in high-temperature and high-salt environments, and has better interfacial activity, which can greatly improve the recovery rate of crude oil. The shortcomings of existing quantum dots in low-permeability and ultra-low-permeability reservoirs, such as poor dispersion stability, insufficient ability to reduce interfacial tension, and poor effect of improving wettability, are overcome.
[0023] (7) The nitrogen-doped quantum dots of the present invention have a simple preparation process, the raw materials are cheap and readily available, can be mass-produced, are easy to store and transport, have outstanding economic benefits, and have broad prospects for industrial application.
[0024] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The microscopic morphology of nitrogen-doped quantum dots.
[0026] Figure 2 This is the cross-sectional thickness diagram of the quantum dots.
[0027] Figure 3 Fluorescence emission spectra of nitrogen-doped quantum dots under different excitation wavelengths.
[0028] Figure 4 Viscoelasticity of the interface film between nitrogen-doped quantum dots and crude oil.
[0029] Figure 5 This is a diagram showing the oil displacement effect of nitrogen-doped quantum dots. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] Example 1
[0032] A novel method for preparing nitrogen-doped quantum dots:
[0033] (1) Add 5 g of citric acid and 1 g of urea into a container, seal and stir for 10 min in a water bath at 45°C to mix the materials evenly.
[0034] (2) Add 1 g of hexadecylamine polyoxyethylene ether to a vessel at 60°C in a water bath, stir until it becomes a light yellow block, and then transfer to a high-temperature and high-pressure reactor. Set the temperature to 170°C and continue heating for 50 minutes to allow the three substances to fully pyrolyze and react, and initially obtain a black solid product.
[0035] (3) The black solid product is ground into powdery particles and then dispersed in n-hexane, washed to preliminarily remove unreacted substances. Anhydrous ethanol is then added and placed in an ultrasonic instrument for multiple washings until the anhydrous ethanol is clear, and then dried to obtain a black powdery product.
[0036] (4) The black powder product was dissolved in deionized water, filtered and purified multiple times using a 0.22 micron filter membrane, and the obtained black liquid was transferred to a 100KD ultrafiltration tube and placed in a centrifuge at a speed of 4000r / min for 20min to remove large particles. The ultrafiltration outer tube clear liquid was added to a dialysis bag with a molecular weight cutoff of 1000Da, sealed and placed in deionized water for continuous dialysis for 48h, and the water was changed every 6h to completely remove the unreacted precursor small molecules; finally, the solution in the dialysis bag was dried to obtain a black powder solid, which was the nitrogen-doped quantum dot 1.
[0037] Example 2
[0038] A novel method for preparing nitrogen-doped quantum dots:
[0039] (1) Add 7.5 g of citric acid and 1.5 g of urea into a container, seal and stir for 10 min in a water bath at 45°C to mix the materials evenly.
[0040] (2) Add 1.5 g of ethylamine polyoxyethylene ether to a vessel at 60° C. in a water bath, stir until it becomes a light yellow block, and then transfer to a high-temperature and high-pressure reactor. Set the temperature to 180° C. and continue heating for 60 min to allow the three substances to fully pyrolyze and react, thereby initially obtaining a black solid product.
[0041] Steps (3) and (4) are the same as in Example 1, and nitrogen-doped quantum dots 2 are finally obtained.
[0042] Example 3
[0043] A novel method for preparing nitrogen-doped quantum dots:
[0044] (1) Add 10 g of citric acid and 2 g of urea into a container, seal and stir for 10 min in a water bath at 45°C to mix the materials evenly.
[0045] (2) Add 2 g of dodecylamine polyoxyethylene ether to a vessel at 65° C. in a water bath, stir until it becomes a light yellow block, and then transfer to a high-temperature and high-pressure reactor. Set the temperature to 190° C. and continue heating for 60 min to allow the three substances to fully pyrolyze and react, thereby initially obtaining a black solid product.
[0046] Steps (3) and (4) are the same as those in Example 1, and nitrogen-doped quantum dots 3 are finally obtained.
[0047] Example 4
[0048] A novel method for preparing nitrogen-doped quantum dots:
[0049] (1) Add 12.5 g of citric acid and 2.5 g of urea into a container, seal and stir for 10 min in a water bath at 45°C to mix the materials evenly.
[0050] (2) Add 2.5 g of octadecylamine polyoxyethylene ether to a vessel at 65° C. in a water bath, stir until light yellow blocks form, and then transfer to a high-temperature and high-pressure reactor. Set the temperature to 200° C. and continue heating for 80 min to allow the three substances to fully pyrolyze and react, thereby initially obtaining a black solid product.
[0051] Steps (3) and (4) are the same as in Example 1, and nitrogen-doped quantum dots 4 are finally obtained.
[0052] The performance test is as follows:
[0053] (1) Microscopic morphology test of nitrogen-doped quantum dots
[0054] The size of the nitrogen-doped quantum dots 1 prepared in Example 1 was observed using a transmission electron microscope (TEM). Figure 1 As shown in FIG. 1 , the particle size is mainly distributed between 5.6 nm and 7.8 nm, and the average particle size is 6.7 nm. The cross-sectional thickness of the nitrogen-doped quantum dot 1 is shown in FIG. Figure 2 As shown, the thickness is mainly distributed between 0.1 nm and 1.3 nm, and the average thickness is 0.7 nm, which indicates that the nitrogen-doped quantum dots prepared in the present invention are typical two-dimensional thin sheets.
[0055] (2) Fluorescence performance test of nitrogen-doped quantum dots
[0056] The nitrogen-doped quantum dots 2 prepared in Example 2 were dispersed in deionized water to prepare a quantum dot solution with a concentration of 100 mg / L. The fluorescence emission spectra of the nitrogen-doped quantum dots 2 under different excitation wavelengths were tested using a fluorescence spectrophotometer. The experimental results are as follows: Figure 3 As shown, the maximum excitation wavelength of nitrogen-doped quantum dots 2 is 280nm, and the maximum emission wavelength is 465nm; it is worth noting that although the fluorescence intensity of the synthesized materials is generally not high within the excitation wavelength range of 300 to 380nm, it still has a strong fluorescence intensity within the excitation wavelength range of 270nm to 290nm, which meets the photoluminescence characteristic of quantum dots and further proves the successful preparation of quantum dots.
[0057] (3) Test on the performance of nitrogen-doped quantum dots in reducing oil / water interface
[0058] Prepare water with different mineralization degrees, 1.0×10 4 mg / L(Na + The concentration is 1×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 5×10 2 mg / L) No. 1#, 2.0×10 4 mg / L(Na + The concentration is 2×104 mg / L, Ca 2+ Mg 2+ The concentration was 1×10 3 mg / L) No. 2#, 3.0×10 4 mg / L(Na + The concentration is 3×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 1.5×10 3 mg / L) No. 3#, 4.0×10 4 mg / L(Na + The concentration is 4×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 2×10 3 mg / L) No. 4#, 5.0×10 4 mg / L(Na + The concentration is 5×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 2.5×10 3 mg / L) No. 5#, 6.0×10 4 mg / L(Na + The concentration is 6×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 3×10 3 mg / L) No. 6#, 7.0×10 4 mg / L(Na + The concentration is 7×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 3.5×10 3 mg / L) No. 7#, 8.0×10 4 mg / L(Na + The concentration is 8×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 4×10 3 mg / L) No. 8#, 9.0×10 4 mg / L(Na + The concentration is 9×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 4.5×10 3 mg / L) No. 9#, 10.0×10 4 mg / L(Na+ The concentration is 10×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 5×10 3 The nitrogen-doped quantum dots 2 prepared in Example 2 were added into different mineralized water to prepare a nitrogen-doped quantum dot solution with a mass concentration of 0.1%, and then placed in an ultrasonic instrument for 20 minutes to completely disperse the solution.
[0059] The crude oil in a certain block was used as the light phase and the quantum dot solution was used as the heavy phase. The interfacial tension between the quantum dot solution and the crude oil was tested with the help of a TX500C interfacial tension meter. The test conditions were as follows: test temperature 65°C, rotation speed 6000rpm, density difference 0.15, and test time 2h.
[0060] The test results of the stable interfacial tension between nitrogen-doped quantum dots 2 and crude oil are shown in Table 1. The experimental results show that the nitrogen quantum dots of the present invention have good interfacial activity and can reduce the interfacial tension to 10 under different mineralized water conditions. -1 mN / m order of magnitude.
[0061] Table 1. Test results of stable interfacial tension between nitrogen-doped quantum dots 2 and crude oil
[0062] serial number Oil / water interfacial tension (mN / m) 1# 0.59 2# 0.66 3# 0.77 4# 0.32 5# 0.43 6# 0.14 7# 0.32 8# 0.67 9# 0.82 10# 0.91
[0063] (4) Test on the improvement of rock wettability by nitrogen-doped quantum dots
[0064] The mineralization degree is 5.0×10 4 mg / L(Na + The concentration is 5×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 2.5×10 3 mg / L) of mineralized water, the nitrogen-doped quantum dots 2 prepared in Example 2 are added to the mineralized water to prepare two 100ml quantum dot solutions with a mass concentration of 0.1%. The oleophilic rock slices and the hydrophilic rock slices are respectively immersed in two quantum dot solutions, sealed and placed in a 65°C oven for continuous aging, and the rock slices are taken out after 1, 3, 5, 7, and 14 days, and the solid-water-oil three-phase contact angles on the surfaces of the oleophilic and hydrophilic rock slices are measured using a Krüss DSA100 droplet shape analyzer. The test results are shown in Table 2, and the results show that the nitrogen-doped quantum dots of the present invention can be adsorbed on the surface of the rock, and the surface of the oleophilic rock slices changes from oil-wet to water-wet, and the surface of the hydrophilic rock slices changes from water-wet to strongly water-wet. This proves that the nitrogen quantum dots of the present invention have the ability to improve the wettability of rocks.
[0065] Table 2. Modification effect of nitrogen-doped quantum dots on rock wettability
[0066] Rock flake type Original contact angle 1d 3d 5d 7d 14d Oil-wet rock slice 147.3° 83.9° 68.9° 57.9° 42.5° 40.9 Hydrophilic rock slice 54.6° 45.8° 43.7° 35.0° 25.3° 22.4°
[0067] (5) Test on improving oil / water interface viscosity by nitrogen-doped quantum dots
[0068] The nitrogen-doped quantum dots 2, OP-10 quantum dots, and polyethylene glycol quantum dots prepared in Example 2 were used as experimental objects. The preparation method of OP-10 quantum dots is to replace ethylamine polyoxyethylene ether with an equal amount of OP-10 on the basis of Example 2, and the prepared quantum dots are OP-10 quantum dots. Similarly, polyethylene glycol quantum dots are prepared by replacing ethylamine polyoxyethylene ether with an equal amount of polyethylene glycol on the basis of Example 2. The experimental method is as follows:
[0069] 5 ml of deionized water and 5 ml of kerosene were dripped into a 15 ml reagent tube. Quantum dot solutions of different concentrations (20, 40, 60, 80, 100 mg / L) were prepared using anhydrous ethanol as the solvent, and the viscosity of different quantum dot solutions was measured at 65 °C using a viscometer. Subsequently, quantum dot solutions of different concentrations were dripped into the reagent tube, and when the quantum dots did not change during the enrichment process at the oil / water interface, the viscosity of the enriched layer at the oil / water interface was measured using a viscometer at 65 °C.
[0070] The experimental results are shown in Table 3. It can be seen that the viscosity of the oil / water interface enrichment layer after adding OP-10 quantum dots and polyethylene glycol quantum dots did not change significantly; after adding nitrogen-doped quantum dots 2, the viscosity of the oil / water interface enrichment layer was significantly increased compared with the solution viscosity. This phenomenon is conducive to achieving efficient flow control, increasing the swept volume of water-driven oil reservoirs, and thus slowing down the occurrence of viscous fingering. This shows that the nitrogen-doped quantum dots prepared by the present invention can spontaneously enrich the oil / water interface to form a colloidal layer with increased local viscosity, which is conducive to fluidity control, preventing the occurrence of viscous fingering, and achieving efficient fluidity control, while other quantum dots such as OP-10 quantum dots and polyethylene glycol quantum dots do not have such an effect.
[0071] Table 3 Nitrogen doped quantum dots improve the viscosity of the enriched layer
[0072]
[0073] (6) Test of nitrogen-doped quantum dots to enhance the strength of oil / water interface films
[0074] Using deionized water as solvent, nitrogen-doped quantum dots 2 prepared in Example 2 were used to prepare nitrogen-doped quantum dot solutions with concentrations of 0 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L. The viscoelasticity of the interface film between the novel nitrogen-doped quantum dot solutions of different concentrations and crude oil was measured using a Krüss DSA100 drop shape analyzer. The experimental results are shown in Figure 4As shown in the figure, as the concentration of nitrogen-doped quantum dot solution increases, the higher the enrichment of quantum dots at the oil / water interface, the greater the strength of the oil / water interface film. Based on the elastic properties of nitrogen-doped quantum dots, the ability of the oil / water interface film to recover and block deformation is enhanced, and the strength of the oil / water interface film is improved. This phenomenon helps to improve the oil / water mobility ratio, expand the swept volume of water flooding, and improve the microscopic oil displacement efficiency.
[0075] (7) Nitrogen-doped quantum dots enhanced oil recovery performance test
[0076] The mineralization degree is 5.0×10 4 mg / L(Na + The concentration is 5×10 4 mg / L, Ca 2+ Mg 2+ The concentration was 2.5×10 3 mg / L) of mineralized water, the nitrogen-doped quantum dots 2 of Example 2 were added to the mineralized water to prepare a nitrogen-doped quantum dot solution with a mass concentration of 0.1%. The artificial core with porosity of 19.8% and water permeability of 5 mD was installed in the core holder. At 65 °C, the mineralization was 5.0×10 4 Under the action of a constant flow pump, the mineralized water of 0.02 ml / min was used to displace the core. When the volume of the injected mineralized water was twice the pore volume of the core, crude oil was used to continue displacing the core at the same displacement rate until no water was produced. After calculation, the oil saturation of the core was 67%. The oil-saturated core and the core holder were aged at 65°C for 48 hours, and then the core was water-flooded at a rate of 0.02 ml / min. When the volume of mineralized water was 0.75 PV, the water content of the output fluid was 98%. Subsequently, the quantum dot solution was used to system-flood the core at a rate of 0.02 ml / min. After the volume of the quantum dot solution was 0.6 PV, the valves at both ends of the core holder were closed to soak the well. After 48 hours, the valves at both ends of the core holder were opened, and the mineral water was displaced at a rate of 0.02 nm / min to displace the core for subsequent water flooding until the output fluid was oil-free. The displacement results are shown in the figure. Figure 5 shown.
[0077] The experimental results show that the water flooding stage is affected by the low oil-water mobility ratio and viscous fingering, and the crude oil recovery rate is only 35.87%. During the injection process of the system flooding stage, the displacement pressure continues to increase, and oil is produced at the outlet, indicating that the nitrogen-doped quantum dot material acts on the oil / water interface, improves the wettability of the rock, increases the capillary force, and improves the efficiency of crude oil displacement. The crude oil recovery rate in this stage increased by 9.58%. After the post-drive water flooding was injected at 2.1PV, no more oil was produced, the water content reached 100%, and the crude oil recovery rate was 11.67%. During the entire displacement process, the system flooding and subsequent water flooding increased the crude oil recovery rate by 21.25%, and the cumulative recovery rate was 57.12%.
[0078] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing nitrogen-doped quantum dots, characterized in that: The following steps are involved: S1. Mix the carbon source and the nitrogen source, and stir them in a sealed container in a water bath at 45° C. for several minutes to uniformly mix the materials to obtain a mixture; S2. Add alkylamine polyoxyethylene ether to the mixture in a water bath at 55-65°C, seal and stir for 10-20 minutes to form a light yellow block, then transfer to a high temperature and high pressure reactor, heat to 150-220°C and keep constant for 45-120 minutes to obtain a black solid product; S3, grinding the black solid product into powder and dispersing it in n-hexane, washing it, and preliminarily removing the unreacted substances; then adding anhydrous ethanol and further washing it with ultrasonic waves to obtain a black powder product; S4. Dissolve the black powder product in deionized water, filter and purify it multiple times using a 0.22-micron filter membrane, transfer the obtained black liquid to a 100KD ultrafiltration tube, and centrifuge to remove large particles; add the clear liquid from the ultrafiltration outer tube to a dialysis bag with a molecular weight cutoff of 1000Da, seal it and dialyze it in deionized water to completely remove unreacted raw material small molecules, and finally dry the solution in the dialysis bag to obtain a black powder solid, which is the nitrogen-doped quantum dots.
2. The method for preparing nitrogen-doped quantum dots according to claim 1, characterized in that: The alkylamine polyoxyethylene ether is selected from one or more combinations of ethylamine polyoxyethylene ether, dodecylamine polyoxyethylene ether, hexadecylamine polyoxyethylene ether and octadecylamine polyoxyethylene ether.
3. The method for preparing nitrogen-doped quantum dots according to claim 1, characterized in that: The carbon source is citric acid, and the nitrogen source is urea.
4. The method for preparing nitrogen-doped quantum dots according to claim 3, characterized in that: The mass ratio of the alkylamine polyoxyethylene ether to the nitrogen source is 1:
1.
5. The method for preparing nitrogen-doped quantum dots according to claim 1, characterized in that: In step S4, the centrifugal separation is performed at a speed of 4000 r / min and a time of 20 min.
6. A nitrogen-doped quantum dot, characterized in that: The preparation method is as described in any one of claims 1 to 5.
7. A method for applying nitrogen-doped quantum dots to oil reservoirs as claimed in claim 6, characterized in that: A nitrogen-doped quantum dot dispersion with a mass percentage concentration of 0.05-0.1% is prepared using on-site injection fluid; the nitrogen-doped quantum dot dispersion is injected into the target reservoir, the well is kept cold for 1-2 days, and then the well is opened for production.
8. The method for applying nitrogen-doped quantum dots to oil reservoirs according to claim 7, characterized in that: The on-site injected fluid is supercritical CO2 or formation water.
Citation Information
Cited By
Two-dimensional nano-carbon quantum chip based on oxidation cutting and preparation method and application of two-dimensional nano-carbon quantum chip
CN120964780A